Analysis of Syntactic Errors in the Arabic Learning Companion Book “Al Kamil” Based on the Independent Curriculum: Analisis Kesalahan SiAnalisis Kesalahan Sintaksis Buku Pendamping Pembelajaran Bahasa Arab MI Kelas IV Berbasis Kurikulum Merdekantaksis Buku Pendamping Pembelajaran Bahasa Arab “Al Kamil” Berbasis Kurikulum Merdeka - Pradnya Paramita, Nurhapsari; Aulia Zulfatun Akhda; Sri Fatimah; Syafia Romadhona (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2024)
There are still many things that could be improved in writing Arabic, especially in terms of syntax or the rules of nahwu and short in Arabic language learning companion books, which can affect the quality of learning for students. The method used is qualitative, with primary data collection techniques carried out through interviews and documentation. Meanwhile, secondary data was collected through documentation and literature study by reviewing books and articles. This book found many syntactic errors in the material, such as reading texts, titles, homework, and evaluation questions. The accompanying language learning book found as many as 36 syntactic errors. Arabic Al-Kamil. These errors are in the form of: errors in the use of dlomir, hamzah, i''rob which affect the harokat, mufrodat, idlofah structure and so on. Keywords: HOTS (Higher Order Thinking Skill), translating text, RADEC learning model, Insya’ learning.